Irrigation performance: Ethiopia - Tadesse, Mulugeta; Mohammed, I.; Schmitter, Petra; Dembélé, Moctar (International Water Management Institute, 2025)
The new WaPOR tool enhances the Irrigation Management Information System of Ethiopia (IMISET) by adding functionalities that improve assessment of crop water requirements, agricultural water use and irrigation performance indicators, while also enabling the identification low-performing or non-functional irrigation systems.